(untitled) (Conference Zone, 2022)
Today, along with all sectors, the emphasis has intensified on the development of innovative information technology in the direction of insurance and thereby creating opportunities for customers. The decision of our country’s administrator on October 23, 2021, "Additional measures to digitize the insurance market and improve the life insurance sector" is significant as it aims to take this work to a new phase.